Java 2 graphics - Griffith, Arthur; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
In this program, the author uses practical examples to demonstrate Java programming as it applies to the creation and manipulation of graphic objects
Title from container
Training CD
Contains 74 movies with total time 6 hours
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Java (Computer program language); Computer graphics